Settlement of Customary Land Disputes Due to Overlapping Customary Land Releases in Skouw Sae Village Muara Tami District Jayapura City - Tanati, Daniel; Rongalaha, Johan (Journal of Progressive Law and Legal Studies, 2025)
Land disputes in Skouw Sae Village, Muara Tami District, Jayapura City, still occur. The purpose of this study is to determine the process of resolving customary land disputes related to the release of overlapping customary land and to determine the obstacles faced in the process of resolving customary land disputes related to the release of overlapping customary land in Skouw Sae Village, Muara Tami District, Jayapura City. The approach used in this study is the normative and empirical legal approach, which refers to laws, literature, written regulations, or other secondary legal materials and sees the reality that occurs in the field. The results of this study reveal that the process of resolving customary land disputes related to the release of overlapping customary land in Skouw Sae Village is through deliberation led by the Customary Head or Customary Figure (Ondoafi), witnessed by the village head, local village head/sub-district head, then the disputing parties are brought together by bringing written evidence of a customary land release letter which is proof of ownership of the customary land. Meanwhile, the obstacles faced in the process of resolving customary land disputes related to the release of overlapping customary land can be seen from two factors, namely internal factors and external factors, where the internal factor is because the disputing parties want to win on their own, each insists on defending their property, and the external factor is the interference of external parties which worsens the problems that occur on both sides.